Pengelompokkan dan Ketidakmiripan Dua Belas Aksesi Kelapa (Cocos nucifera L.) Asal Beberapa Provinsi [Grouping and Dissimilarity Among Twelve Coconut Accessions (Cocos Nucifera L.) From Some Provinces] - nFN Miftahorrachman; Muhammad Roiyan Romadhon; nFN Rahma; Jeanette Kumaunang (Buletin Palma, 2020)
The spread of coconut plants are almost in most regions in Indonesia, which causes considerable genetic diversity and is an opportunity as genetic material for improvement of national coconut plants and opportunity as genetic material for the improvement of national coconut plants and can be used as parents in the assembly of new hybrid varieties. This research was conducted from 2017 to 2018 in several provinces in Indonesia including provinces of West Sumatra, Jambi, East Kalimantan, South Kalimantan and North Sulawesi. The purpose of this study was to study the level of variation of coconut germplasm in Indonesia, organize and classify variations, and classify accessions by considering various characters that can be used as parents. Grouping and dissimilarity are based on twelve morphological characters and fruit components, namely the number of leaves (NL), number of bunches/trees (NBT), number of fruits/bunches (NFB), weight of whole fruit (WWF), whole fruit polar circumference (WFPC), whole fruit equatorial circumference (WFEC), weight of fruit without husk/seed (WFWHS), polar seed circumference (PSC), equatorial seed circumference (ESC), weight of fruit without water (WFWW), weight of endosperm(WE), and thick of endosperm (TE).The data obtained were then analyzed using a divisive or top-down clustering method (hierarchial cluster) by partitioning at least two classes that were the least similar. The data is processed using R. 3.5.1 software. Determination of the average distance (average linkage) obtained from the average dissimilarity coefficient data from each of the accessions tested.The results showed the twelve coconut accessions formed four groups at a 32% dissimilarity. Group I consisted of one accession (Bram Itam), group IIconsisted ofthree accessions are  (Pesisir Selatan, Kapuah Jaya, Muara Jawa) group IIIconsisted ofeight accessions (Tanjung Solok, Labuan Uki, Pindolili, Mekar Sari, Betara Kanan, Siri Hulu, Tamban Bangun, Pengabuan). Eigen value in the main component 1 (KU1)> 1 with a variation of 60.60% with the number of bunches/trees, whole fruit polar circumference, weight of fruit without husk/seed, polar seed circumference, equatorial seed circumference, weight of fruit without water, dan thick of endospermand hybridisation is carried out so that it can produce superior hybrids.ABSTRAKPenyebaran tanaman kelapa hampir di sebagian besar daerah di Indonesia, sehingga menyebabkan keragaman genetik yang cukup besar dan merupakan peluang sebagai materi genetik untuk perbaikan tanaman kelapa nasional dan dapat dijadikan sebagai tetua dalam perakitan varietas hibrida baru. Penelitian ini dilaksanakan pada tahun 2017 sampai 2018 di beberapa Provinsi di Indnesia meliputi Propinsi Sumatera Barat,  Jambi,  Kalimantan Timur, Kalimantan Selatan, dan Sulawesi Utara. Tujuan penelitian ini untuk mengetahui tingkat variasi plasma nutfah kelapa di Indonesia, mengidentifikasi dan mengklasifikasikan variasi, dan mengelompokkan aksesi dengan mempertimbangkan beberapa karakter yang dapat dijadikan sebagai tetua. Pengelompokan dan ketidakmiripan  didasarkan pada duabelas karakter  morfologi dan komponen buah, yaitu jumlah daun (JD), jumlah tandan/pohon (JT), jumlah buah/tandan (JBT), berat buah utuh (BBU), lingkar polar buah utuh (LPBU), lingkar equatorial buah utuh (LEBU), berat buah tanpa sabut/biji (BBTS), lingkar polar biji (LPB), lingkar equatorial biji (LEB), berat buah tanpa air (BBTA), berat daging buah (BD), dan tebal daging (TD). Data yang diperoleh kemudian dianalisis dengan metode pengelompokan divisive atau top-down (hierarchial cluster) dengan mempartisi klaster minimal dua klaster yang paling tidak mirip. Data diolah dengan menggunakan software  R. 3.5.1. Penentuan jarak rata-rata (average linkage) yang diperoleh dari rataan data koefisien ketidakmiripan dari masing-masing aksesi yang diuji. Hasil penelitian menunjukkan  ke dua belas aksesi kelapa tersebut membentuk empat kelompok pada ketidakmiripan 32%. Kelompok I  terdiri dari satu aksesi (Bram Itam), kelompok II terdiri dari aksesi (Pesisir Selatan, Kapuah Jaya, Muara Jaawa), dan kelompok III satu aksesi (Tanjung Solok, Labuan Uki, Pindolili, Mekar Sari, Betara Kanan, Siri Hulu, Tamban Bangun, Pengabuan). Nilai eigen value pada komponen utama 1 (KU1) > 1 dengan keragaman sebesar 60,60% dengan karakter jumlah daun, jumlah tandan, lingkar polar buah utuh, berat buah tanpa serabut, lingkar polar biji, lingkar ekuatorial biji, berat buah tanpa air, dan berat daging yang dijadikan sebagai karakter seleksi terhadap keragaman yang tinggi untuk dijadikan sebagai tetua dan dilakukan hibridisasi sehingga dapat menghasilkan hibrida superior.